2004
DOI: 10.1080/01926230490260655
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanisms Underlying the Testicular Toxicity of Oxfendazole in Rats

Abstract: To clarify the mechanisms underlying the testicular toxicity of oxfendazole (OX), adult Wistar rats were orally administered a dose of 100 mg/kg/day for 3, 7, or 14 days. Assays of sex-related hormones showed a significant decrease in only the estradiol serum level at days 3 and 7, as compared with the control group. Histopathologically, marked degeneration of meiotic spermatocytes was observed in stage XIV-I seminiferous tubules from day 3 onwards, and these spermatocytes gave positive results on terminal deo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
1
9
0
4
Order By: Relevance
“…Supporting evidence for the accumulation of neutral lipids in the latter may be found in the histologic observations presented by other authors, in which they show lipid droplets in the Sertoli cell cytoplasm under several pathological conditions that lead to spermatogenesis arrest [48,49]. This is consistent with the fact that damaged or dead germ cells are phagocytosed by Sertoli cells, which hydrolyze and are able to reutilize some of the resulting elements [50][51][52].…”
Section: Testicular Lipids In Cryptorchidismsupporting
confidence: 76%
“…Supporting evidence for the accumulation of neutral lipids in the latter may be found in the histologic observations presented by other authors, in which they show lipid droplets in the Sertoli cell cytoplasm under several pathological conditions that lead to spermatogenesis arrest [48,49]. This is consistent with the fact that damaged or dead germ cells are phagocytosed by Sertoli cells, which hydrolyze and are able to reutilize some of the resulting elements [50][51][52].…”
Section: Testicular Lipids In Cryptorchidismsupporting
confidence: 76%
“…Mebendazole interacting with tubulin interferes with the assemblage of the mitotic apparatus in the parasite cells, thus causing a possible genotoxic activity leading to chromosomal malsegregation [29]. Also, Okamura et al [30] suggested that oxfendazole induces apoptosis of meiotic spermatocytes, most probably due to disruption of the microtubules, and degeneration of the Sertoli cells. Uppala et al [31] indicate that chemicals can induce cellular and chromosomal alterations, inducing early events in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…По сведениям литературы, микроядра и протру-зии могут рассматриваться как биомаркеры канце-рогенного эффекта и быть самым ранним проявле-нием риска рака ротовой полости, лимфатических узлов, грудной клетки [18][19][20]. По нашим данным, максимальные кариологические (цитологические) изменения были выражены у матерей (1-е поколе-ние) с новообразованиями, в том числе злокаче-ственными (щитовидной железы, молочной железы) и перенесших оперативное лечение по поводу этих заболеваний.…”
Section: результаты и обсуждениеunclassified